Quantifying the long-term interplay between photoprotection and repair mechanisms sustaining photosystem II activity. Issue 5 (16th March 2022) - Saccon, Francesco; Wilson, Sam; Morey-Burrows, Felix S.; Ruban, Alexander V.
Abstract : The photosystem II reaction centre (RCII) protein subunit D1 is the main target of light-induced damage in the thylakoid membrane. As such, it is constantly replaced with newly synthesised proteins, in a process dubbed the 'D1 repair cycle'. The mechanism of relief of excitation energy pressure on RCII, non-photochemical quenching (NPQ), is activated to prevent damage. The contribution of the D1 repair cycle and NPQ in preserving the photochemical efficiency of RCII is currently unclear. In this work, we seek to (1) quantify the relative long-term effectiveness of photoprotection offered by NPQ and the D1 repair cycle, and (2) determine the fraction of sustained decrease in RCII activity that is due to long-term protective processes. We found that while under short-term, sunfleck-mimicking illumination, NPQ is substantially more effective in preserving RCII activity than the D1 repair cycle ( Plant. Cell Environ. 41, 1098–1112, 2018). Under prolonged constant illumination, its contribution is less pronounced, accounting only for up to 30% of RCII protection, while D1 repair assumes a predominant role. Exposure to a wide range of light intensities yields comparable results, highlighting the crucial role of a constant and rapid D1 turnover for the maintenance of RCII efficiency. The interplay between NPQ and D1 repair cycle is crucial to grant complete phototolerance to plants under low and moderate light intensities, and limit damage to photosystem II under high light. Additionally, we disentangled and quantified the contribution of a slowly reversible NPQ component that does not impair RCII activity, and is therefore protective.